Individual and Neighborhood Characteristics of Children Seeking Emergency Department Care for Firearm Injuries Within the PECARN Network. (29th May 2017) - Carter, Patrick M.; Cook, Lawrence J.; Macy, Michelle L.; Zonfrillo, Mark R.; Stanley, Rachel M.; Chamberlain, James M.; Fein, Joel A.; Alpern, Elizabeth R.; Cunningham, Rebecca M.; ,
Abstract: Objective: The objective was to describe the characteristics of children seeking emergency care for firearm injuries within the PECARN network and assess the influence of both individual and neighborhood factors on firearm‐related injury risk. Methods: This was a retrospective, multicenter cross‐sectional analysis of children (<19 years old) presenting to 16 pediatric EDs (2004–2008). ICD‐9‐CM E‐codes were used to identify and categorize firearm injuries by mechanism/intent. Neighborhood variables were derived from home address data. Multivariable analysis examined the influence of individual and neighborhood factors on firearm‐related injuries compared to nonfirearm ED visits. Injury recidivism was assessed. Results: A total of 1, 758 pediatric ED visits for firearm‐related injuries were analyzed. Assault (51.4%, n = 904) and unintentional injury (33.2%, n = 584) were the most common injury mechanisms. Among children with firearm injuries, 68.3% were older adolescents (15–19 years old), 82.3% were male, 68.2% were African American, and 76.3% received public insurance/were uninsured. Extremity injuries were most common (75.9%), with 20% sustaining injuries to multiple body regions, 48.1% requiring admission and 1% ED mortality. Multivariable analysis identified firearm injury risk factors, including adolescent age (p < 0.001), male sex (p < 0.001), non‐Caucasian race/ethnicity (p < 0.001), public payer/uninsured status (p < 0.001), and higher levels of neighborhood disadvantage (p < 0.001). Among children with firearm injuries, 12‐month ED recidivism for any reason was 22.4%, with < 1% returning for another firearm injury. Conclusion: Among children receiving ED treatment within the PECARN network, there are distinct demographic and neighborhood factors associated with firearm injuries. Among younger children (<10 years old), unintentional injuries predominate, while assault‐type injuries were most common among older adolescents. Overall, among this PECARN patient population, male adolescents living in neighborhoods characterized by high levels of concentrated disadvantage had an elevated risk for firearm injury. Public health efforts should focus on developing and implementing initiatives addressing risk factors at both the individual and the community level, including ED‐based interventions to reduce the risk for firearm injuries among high‐risk pediatric populations.